Experimental study about the influence of adhesive stiffness to the bonding strengths of adhesives for ceramic/metal targets - W. Seifert; E. Strassburger; S. Grefen; S. Schaare (Defence Technology, 2016)
The aim of the investigations presented here was to understand how the stiffness of the adhesive affects the failure of ceramic tiles adhered to metallic backings. The working hypothesis was that varying the adhesive stiffness could have the same effect on the ballistic performance as a variation of the adhesive thickness. Two different projectile/target combinations were utilized for ballistic tests in order to generate extremely different loading conditions. With targets consisting of 6 mm aluminum oxide ceramic and 6 mm aluminum backing, complete penetration occurred in each test with 7.62 mm tungsten carbide core AP ammunition at an impact velocity of 940 m/s. In contrast, with ceramic tiles of 20 mm thickness on 13 mm steel backing, no penetration of the ceramic occurred at the impact of a 7.62 mm ball round at 840 m/s. Four different types of adhesive (high-strength till high-flexible) were tested in both configurations. The elongation of the adhesive layer, the deformation of the metallic backing and the failure of the ceramics were observed by means of a high-speed camera during the projectile/target interaction. The results of the ballistic tests showed that a higher fracture strain caused a larger deformation of the backing compared to adhesives, which exhibit a high tensile strength and low fracture strains. The experimental results indicate that the damage behavior of the ceramic/metal composites depends on the absolute elongation of the adhesive layer. This can be controlled either by the thickness or the stiffness of the bonding layer.